Conversion of cast carbon steel into composite material - E. I. Marukovich; S. M. Usherenko; Javad Yazdani-Cherati; Yu. S. Usherenko (Литьë и металлургия)
Experimental estimates of the strength properties of a composite material based on carbon steel 45, created by piercing matrix steel in the mode of superdeep penetration by streams of powder particles, have been performed. Pulsed dynamic action by streams of powder particles and subsequent heat treatment converts steel into a fiber composite material.